A Content Analysis of Published Articles in Journal of Anthropology of Sport and Physical Education from 2017 to 2018 - Marin Corluka; Milica Bjelica (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
Journal of Anthropology of Sport and Physical Education (JASPE) is a scientifi c journal that exists for two years and has so far released 87 scientifi c papers in 5 editions. The papers are from various fi elds of sports science - anthropology, sports marketing and other areas of sports. In this paper, we classifi ed works by fi elds, method of address analysis and found that the most numerous works from the anthropology of sports, which are the most cited and best quoted in scientifi c databases. We have also established that the published works had themes - the most up-to-date tendencies in sports science. These research can be useful for further theoretical research, as well as for theoreticians. The authors of the works are researchers from all over the world, as well as the editorial board. The JASPE includes works from exact disciplines, primarily anthropology of sports, as well as from social sciences, thus achieving a synergistic eff ect.